Referrals for uncomplicated lower back pain: A cluster parallel randomised trial of patient-centred communication to improve the management of acute back pain in primary care. A study protocol - Schedlbauer, Angela; Burggraf, Larissa; Hueber, Susann; Terzakis-Snyder, Irini-Alexia; Kühlein, Thomas; Roos, Marco (BMJ Open, 2019)
Introduction Low back pain (LBP) is one of the most frequent encounters in General Practice. Investigation and referral remain common despite the self-limiting character of episodes that are not largely attributable to specific underlying injuries. Identifying patients' ideas, concerns and expectations (ICE) is a well-established element within consultation skills training and has been shown to improve prescribing. It can be a powerful communication tool setting the base for transferring and adjusting adequate clinical information. This study aims to evaluate whether ICE can decrease unnecessary medicine in the management of acute LBP in primary care. Methods and analysis Research question: Does ICE training intervention have an effect on doctors' referrals of patients suffering from acute LBP? Population: Recruitment to this parallel cluster randomised trial will take place among general practitioners belonging to four independent practice networks in Northern Bavaria/Germany. Intervention: At baseline, 24 out of 48 doctors will be randomly assigned to take part in a 1-day training session covering theoretical background and clinical implementation of patient-centred communication by stimulating ICE. They will also be given access to a web-based supporting tool for reflective practice on their communication skills. Comparison: GPs in the control group will continue consultations as usual. Outcome: Outcome measures are referrals to diagnostic imaging, physiotherapy and specialists obtained from routine practice data, compared between intervention and control group. Time: Referrals of patients consulting their doctors for documented LBP will be monitored up to 3 months after the ICE training intervention. Ethics and dissemination Ethical approval for the study was obtained by the Ethics Committee of the University Erlangen-Nuremberg (296_17B). Results will be disseminated by conference presentations and journal publications. Trial registration number The trial is registered in clinicaltrials.gov (NCT03711071).
CRIS-Team Scopus Importer:2019-11-08
Keywords: communication; consultation; diagnosis; doctor-patient relationship; information exchange; low back pain; medical education; over investigation; primary care; shared decision-making